2020
DOI: 10.37358/rc.20.6.8212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Nutrients, Enzyme Activities and Microbial Composition in Vegetable-Polygonatum Odoratum Rotation Regimes

Abstract: The rotation regimes significantly alter soil properties, however, understanding the effect of crop rotation in various crops system was currently limited. The aim of this research was to reveal the variation in crop productivity, soil nutrients, enzyme activities, and bacterial community composition in vegetable-Polygonatum odoratum rotation horticulture. Thus, a 2-year field experiment was carried out under the P.odoratum-P.odoratum rotation (CC) and vegetable-P.odoratum rotation (FC) system through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The phenolic acids are detrimental to the rhizosphere soil environment and can change the soil microbial community [ 9 ]. Phenolic acids have a hydroxyl group and a carboxyl group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenolic acids are detrimental to the rhizosphere soil environment and can change the soil microbial community [ 9 ]. Phenolic acids have a hydroxyl group and a carboxyl group.…”
Section: Discussionmentioning
confidence: 99%
“…An early study showed that the low-molecule-weight substances extracted from the P. odoratum rhizosphere soil solutions exhibited an obvious self-poison effect on P. odoratum seedling growth and allelopathy effect on the rhizome spore germination rate [ 8 ]. Our recent studies have revealed that the Polygonatum CMP could be alleviated or eradicated under the rotation regimes or with an aeroponic system [ 9 , 10 ], and the miRNAs-regulated genes participating in the sugar and phenylpropanoid metabolism have been enriched through the mircoRNA sequencing on the CC and the first cropping (FC) P. odoratum [ 11 ]. All these results prompted that the root rot in P. odoratum was likely related to the phenolic acid metabolism.…”
Section: Introductionmentioning
confidence: 99%